Local Existence of Bounded Solutions to the Degenerate Stefan Problem with Joule's Heating (Journal of Partial Differential Equations, 1996)
This paper deals with the degenerate Stefan problem with Joule's heating, which describes the combined effects of heat and electrical current Rows in a metal. The local existence of a bounded weak solution for the problem in proved. Also a degenerate thermistor problem with continuous conductivity is considered.